2002
DOI: 10.1074/jbc.m205945200
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Mobilization Evoked by Hepatocellular Swelling Is Linked to Activation of Phospholipase Cγ

Abstract: Recovery from swelling of hepatocytes and selected other epithelia is triggered by intracellular Ca 2؉ release from the endoplasmic reticulum, which leads to fluid and electrolyte efflux through volume-sensitive K ؉ and Cl ؊ channels. The aim of this study was to determine the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
34
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 37 publications
2
34
0
Order By: Relevance
“…Neither can we exclude the possibility that product(s) of phospholipase C (PLC)-mediated PIP 2 hydrolysis, such as diacylglycerol or inositol 1,4,5-trisphosphate exert such a role. Interestingly, PLC is activated by hepatocellular swelling (1,32). The present study was therefore designed to explore the role of the PIP 2 /PLC signaling pathway in the modulation of resting and swelling-activated KCNQ1-like K ϩ currents in short-term cultured rat hepatocytes and to determine whether these channels contribute to RVD-induced whole organ K ϩ flux in the intact liver.…”
mentioning
confidence: 99%
“…Neither can we exclude the possibility that product(s) of phospholipase C (PLC)-mediated PIP 2 hydrolysis, such as diacylglycerol or inositol 1,4,5-trisphosphate exert such a role. Interestingly, PLC is activated by hepatocellular swelling (1,32). The present study was therefore designed to explore the role of the PIP 2 /PLC signaling pathway in the modulation of resting and swelling-activated KCNQ1-like K ϩ currents in short-term cultured rat hepatocytes and to determine whether these channels contribute to RVD-induced whole organ K ϩ flux in the intact liver.…”
mentioning
confidence: 99%
“…PLA 2 and Src kinase have also been implicated in the activation of TRPCmediated SOC and ROC activities (Hisatsune et al 2004;Bolotina and Csutora 2005;Vazquez et al 2004b). There is also evidence that indicates PLC may be MS (Brophy et al 1993), with some reports indicating that the mechanosensitivity depends upon Ca 2+ influx (Basavappa et al 1988;Matsumoto et al 1995;Ryan et al 2000;Ruwhof et al 2001;Alexander et al 2004) and others indicating independence of external Ca 2+ and Ca 2+ influx (Mitchell et al 1997;Rosales et al 1997;Moore et al 2002). In either case, the combined evidence indicates that mechanical forces transduced by MscCa and/or by MS enzymes may modulate the gating of all TRP channels.…”
Section: Discussionmentioning
confidence: 87%
“…However, while there are reports that PLC can be mechanically stimulated independent of external Ca 2+ (Rosales et al 1997;Mitchell et al 1997;Moore et al 2002), there are more cases that indicate that the mechanosensitivity of PLC derives from stimulation by Ca 2+ influx via MscCa (Matsumoto et al 1995;Ryan et al 2000;Ruwhof et al 2001). In this case, it becomes important to demonstrate that TRPC6 can be mechanically activated in the absence of external Ca 2+ (e.g., using Ba…”
Section: Trpc6 Role In Myogenic Tonementioning
confidence: 99%
“…In this model, we propose that cells subjected to a high osmotic imbalance generate H 2 O 2 upon NAD(P)H oxidase activation (22) promoting Src-mediated PLC␥1 phosphorylation (10,24) leading to IP 3 -sensitive intracellular Ca 2ϩ mobilization (18,51) and subsequent VSOR Cl Ϫ channel activation. On the other hand, cell swelling triggers the release of ATP (23,33), which in turn acts on P2X4 receptors increasing the Ca 2ϩ permeability and thus, modulating the time course of VSOR Cl Ϫ currents (this work).…”
Section: Vsor CLmentioning
confidence: 99%
“…In the same cells, it has been observed that after exposure to a hypotonic solution, these cells respond with a transient increase in NAD(P)H oxidase-dependent H 2 O 2 production (22), [Ca 2ϩ ] i (18) and release of ATP (23). The [Ca 2ϩ ] i increase in these cells induced by extracellular exposure to hypotonicity was demonstrated to be mediated by PLC␥1 phosphorylation (10). More recently, we established in the same cell system that exogenous application of H 2 O 2 induced PLC␥1 phosphorylation in isotonic conditions.…”
mentioning
confidence: 99%